(untitled) (MCIT: Proceedings of International scientific and practical conference, 2019)
On the basis of mathematical model of convective diffusion in a three-layered filter it is formulated a contactinitial- boundary value problem for description of mass transfer of pollution accompanying the sorption processes. It is proposed the algorithm for establishing the estimation of values of sought function (concentration of pollution) at the lower boundary of the filter on the basis of the interpolation of experimental data. It is taken into account that the right end of the interpolation segment is unknown. It is determined the exact solutions of contact-initialboundary value problems of mass transfer with provision for both diffusive and convective mechanisms of transfer as well as sorption processes, which is based on integral transformations over space variables in the contacting regions. Is it designed software and established regularities of convective diffusion process in the three-layered filter.